1995
DOI: 10.1093/ajcn/61.2.279
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of infant body fat by anthropometry and total-body electrical conductivity

Abstract: Measurement of total-body electrical conductivity (TOBEC) has emerged as a rapid, safe, and reproducible method for estimation of infant total body fat (TBF). Agreement of two anthropometric methods [by Dauncey et al (1977) and Weststrate et al (1989)] with TOBEC-TBF was assessed in 435 healthy infants aged 21-365 d. Dauncey-TBF correlated with TOBEC-TBF by r2 = 0.61 and exceeded TOBEC-TBF by 0.14 +/- 0.25 kg in infants< 4 mo of age. Thereafter, TOBEC-TBF exceeded Dauncey-TBF by 0.20 +/- 0.47 kg. We modified D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 13 publications
2
24
1
Order By: Relevance
“…This is in contrast to the results by de Bruin et al (1995), who found that this method overestimated body fatness in infants when total body electrical conductivity was used as the reference method. Their infants were, however, considerably different from our subjects with respect to age and body fatness.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to the results by de Bruin et al (1995), who found that this method overestimated body fatness in infants when total body electrical conductivity was used as the reference method. Their infants were, however, considerably different from our subjects with respect to age and body fatness.…”
Section: Discussioncontrasting
confidence: 99%
“…Two infant studies compared body composition measurements using TOBEC with measurements using an anthropometric technique 1 or an isotope dilution method. 2 Two adult studies compared FFM measured by TOBEC with that measured by densitometry andaor 40 K counting.…”
Section: Introductionmentioning
confidence: 99%
“…A large variety of nondestructive BCA methods have been developed, each with its advantages and shortcomings, such as air-displacement plethysmography (ADP) (6), bioelectrical impedance analysis (BIA) (7), dual-energy x-ray absorptiometry (DXA) (8), total-body electrical conductivity (TOBEC) (9), total body potassium (TBK) (10), isotope dilution (11), skin-fold thickness measurements (SFT) (12), multicompartment models (13), computed tomography (CT) (14), MRI (15), magnetic resonance spectroscopy (MRS) (16), and quantitative magnetic resonance (QMR) (17).…”
mentioning
confidence: 99%